Water Quality Parameters, Dissolved Mineral Levels, and Psoriasis Healing Effects: A Specific Study of Pokhara, Nepal Hot Spring - Hari Sharan Adhikari; Kedar Nath Dhakal; Rameshwar Adhikari (Chemistry and Biochemistry: Research Progress Vol. 2, 2025)
The current study comprised a specific study of water quality parameters and dissolved mineral levels to assess the therapeutic and toxicity states of the hot spring water in a locale of Pokhara, Nepal countryside. People take baths and soak in the hot spring to heal from allergic and fungal ailments, arthritis, musculoskeletal disorders and different skin diseases. The hot spring water bath was reportedly found useful towards healing and relief from itchy skin allergic rashes, and persisting skin disorders but the prolonged soakers of the hot spring also complained the adverse effects such as dandruff, skin blister, dry and inflamed skin, ooze and crust. The hot spring baths were found to impart good healing and relieving effects against psoriasis but the mild skin burn and dandruff were the common side effects. The water quality parameters and mineral levels data above the acceptable range for recreational and swimming purposes showed the necessity of technical moderation to sustain the acceptable levels of hot spring minerals and water quality parameters. The unsuitability of hot spring water for drinking, soaking in and recreational swimming purposes was shown by higher than accepted values of alkalinity (700 ppm), total suspended solids with the size of at least 2 µm (TSS) (50 ppm), total dissolved solids (TDS) (650 ppm), turbidity (13 NTU), soluble carbonate (150 ppm), soluble chloride (250 ppm), surface tension (72.98 Dynes cm-1) and total hardness (880 ppm). The hot spring water showed correspondence to safe utility in terms of the levels of nitrate (undetectable), iron(II) (<0.3 ppm, undetectable), iron(II) (<0.3 ppm, undetectable) and aluminum(III) (<0.3 ppm, undetectable). The healing effects of the hot spring water against musculoskeletal disorders and fungal ailments were found to be associated with its high sulphate level at 400 ppm. The hot spring could be developed as consistently a sulphate-rich spring useful for balneotherapy, wellness and spa tourism, with proper attenuation of water quality parameters and mineral levels at a level of acceptance.